WORKSHOP ON THE USE OF PhET INTERACTIVE SIMULATION TO SUPPORT SCIENCE LEARNING AT SMA NEGERI 2 KAHAYAN TENGAH - Meiliawati, Ruli; Sidauruk, Suandi; Wulandari, Agtri; Ristiyana Puspita Sari, Anggi; Syarpin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
Science learning is closely related to practical activities. However, in certain conditions, practical activities cannot be optimally implemented due to limited tools and materials. PhET Interactive Simulation is a virtual laboratory application that can be utilized in science learning. The objectives of the Workshop on Using PhET Interactive Simulation at SMA Negeri 2 Kahayan Tengah are: 1) to improve teachers' understanding of technology-based learning through PhET Interactive Simulations; 2) to enhance teachers' skills in integrating PhET simulation-based technology into teaching modules; 3) to foster students' interest and motivation in science through learning experiences using PhET simulations. The stages of the workshop include: 1) Preparation Stage: Field surveys, planning, administrative setup, and preparation of supporting facilities; 2) Training Stage: Confirming attendance, conducting Phase I and Phase II training sessions. The outcomes of the workshop can be assessed from participants' satisfaction levels. The satisfaction rate among teachers was 99.5%, categorized as Very Satisfied. Additionally, the quality of teacher-created teaching modules was quite good, indicating that teachers improved their knowledge and skills in developing PhET-integrated teaching modules. Meanwhile, the student satisfaction level reached 87.88%, also classified as Very Satisfied, suggesting a significant increase in student interest and motivation in learning with PhET. In conclusion, this workshop proved to be highly important and beneficial, and it is hoped that similar programs will continue to benefit other teachers in the future.